The Effects of Purslane Consumption on Obesity Indices: A GRADE-Assessed Systematic Review and Meta-Analysis of Randomized Controlled Trials - Vajdi, Mahdi; Hassanizadeh, Shirin; Shojaei-Zarghani, Sara; Bagherniya, Mohammad; Askari, Gholamreza (Journal of food biochemistry, 2023)
Obesity and overweight are among the most significant global health challenges that affect both developed and developing countries, leading to various chronic diseases. Previous studies have reported inconsistent results regarding the effects of purslane supplementation on obesity indices. Therefore, the aim of this study was to perform a meta-analysis on the effects of supplementation with purslane on obesity indices among adults. Comprehensive systematic searches were performed throughout Web of Science, EMBASE, PubMed, Scopus, and Cochrane Library databases up to May 30, 2023. All randomized controlled trials (RCTs) that investigated the impact of purslane supplementation on obesity indices were included into the analysis. The I2 and Cochran’s Q tests were used to assess heterogeneity between studies. The effect sizes were reported as the weighted mean difference (WMD) and 95% confidence intervals (CIs) using a random effects model. The initial search yielded 789 studies, of which seven RCTs were included in analysis. Following purslane supplementation, body weight (BW) (WMD: −0.94 kg, 95% CI: −1.57–−0.31, and P = 0.002) and body mass index (BMI) (WMD: −0.53 kg/m2, 95% CI: −0.88–−0.18, and P: 0.001) decreased significantly. However, this meta-analysis could not show any beneficial effect of purslane supplementation on waist circumference (WC) (WMD: −0.28 cm, 95% CI: −1.47–0.91, and P = 0.23). In addition, there was no linear association between the duration of treatment and sample size with BW, BMI, and WC. In conclusion, this meta-analysis showed a significant effect of purslane supplementation on BMI and BW but not on WC in adults, suggesting that it has the potential to be used therapeutically. Moreover, the combined results of previous RCTs indicate that purslane is a safe and effective intervention for reducing obesity indices in subjects with metabolic syndrome or obesity. As such, the consumption of purslane may have indirectly contributed to the amelioration of clinical symptoms in diseases with metabolic disorders, owing to its impact on some obesity indices. However, given the limitations and the low number of included studies in the present meta-analysis, more large-scale RCTs are needed to shed light on this issue.